Proceso para fortalecer el registro de propiedad intelectual en las instituciones de educación superior (2021)
This methodological note proposes a reference document for the registration of projects developed in higher education institutions (HEI), in which a problem is briefly defined, a synthesis of the evidence is made, possible lines of action are identified, and recommendations are proposed. The main objective is to describe the methodology for the assessment and registration of the intellectual production of students of HEI in ten stages: 1) strengthening knowledge on intellectual property registration in the curricular contents; 2) development of entrepreneurial or research projects in the training environments; 3) implementation of database for projects and innovations registration; 4) official registration of projects in the database; 5) review and evaluation of projects by the institution's intellectual property experts; 6) recommendations for projects requiring adjustments; 7) inclusion of alternatives in the intellectual property registration categories of approved projects; 8) registration of intellectual property in the responsible institutions (Superintendence of Industry and Commerce, Copyright National Directorate); 9) implementation of the projects requiring implementation; 10) dissemination of projects in the different educational institutions. Finally, the process of intellectual property registration is presented as research material for the any type of project management.